Development of chatter control method for application in turning - Ummu Atiqah Khairiyah binti Mohamad (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
This paper presents an analysis of chatter vibration in turning operation. Chatter is a vibration that occurs during machining operations resulting from instability of the cutting process with system responses of the spindle-tool-chuck system. One of the most challenging issues in machining process is to know the chatter characteristics. This Masters dissertation project investigates the performance of permanent magnet (Neodymium) with the power 4500 Gauss in suppressing the chatter phenomenon in turning operation. Several control approaches to the active suppression of machining chatter was examined using a specially constructed turning experiment. To this effect the natural frequencies of different lathe machine-work-tool systems was identified through experimental and FEA modal analyses. Chatter frequencies was recognized and analyzed using a powerful online vibration monitoring system (FFT and DASYLab 5.6 software) attached with the KISTLER accelerometer type 8774A50 and the chip serration frequencies was determined using scanning electron microscope (SEM). Empirical mathematical models of chip serration frequencies and tool life was developed as functions of cutting parameters for different work materials and cutting conditions using Response Surface Methodology (RSM). The comparisons between the magnet and without magnet were made in terms of vibration analysis, chip serration frequency and tool life. Finally an appropriate chatter mathematical model for turning was successfully studied. Based on this model different chatter control techniques for turning was developed and their impact on different machining parameters was tested. This paper also presents the results of turning performance by using parameters from application of Response Surface Methodology (RSM) such as feed rate, cutting speed, and depth of cut by using stainless steel AISI 304 with 120 mm tool overhang and TiN coated carbide insert.